Assessing the Curricula of Political Sciences' Programs at the Palestinian Universities in Accordance with the Academic Standards of Political Sciences - Alaa H. A . Aburedwan (University of Science and Technology, Yemen, 2017)
The study aimed at answering the following key question: Are academic standards of political sciences fulfilled in the curricula of political science programs at the Palestinian universities? Accordingly, the study included a theoretical section that explained the basic concepts of quality in education, and some international experiences adopted for quality assurance of political sciences programs. Then the study analyzed, according to the standard criteria, the curricula of four departments that grant a bachelor's degree in political sciences, based on information published on the departments' sites on the internet, and according to the academic guidebook of each department. The study concluded that the mission and objectives of three departments are clear, while the findings of the analysis showed that there is mismatch of requirements in the Palestinian curricula with academic standards. Most programs are rich with major materials, but need a little adjustment to conform to the standards. The findings also showed a number of negative points in study plans, which do not contain enough credit hours for scientific research, computer applications, and field training, while they have extra credit hours for university requirements. The study made several recommendations to address the problems of the curricula, including: Inviting departments to form committees to ensure quality, to modify the curricula, and develop it in accordance with international standards. Keywords: Academic program, Academic standards, Curricula assessment, Political sciences.